Differences in the metabolism of C4 isotypes in patients with complement activation. - Peake, P W (1989)
The metabolism of the C4 allotypes C4A3,B1 and C4A3,BO was studied in five healthy control subjects and six patients with active immunological disease (five with systemic lupus erythematosus and one with rheumatoid arthritis). The specific aim was to identify any differences in the metabolism of C4A and C4B gene products that may be linked to their documented functional differences in vitro. The fractional catabolic rate of C4A3,B1 in patients was significantly greater than that of C4A3,BO (3.98 +/- 1.37 versus 3.31 +/- 0.85%/h; mean +/- s.d.; P less than 0.05) but there was no difference in control subjects (1.95 versus 1.99%/h). The extravascular:intravascular (EV:IV) distribution ratio of C4A3,B1 was also greater in both patients (1.19 +/- 0.36 versus 0.97 +/- 0.35; P less than 0.01) and controls (0.43 +/- 0.11 versus 0.31 +/- 0.13; P = 0.01). We conclude that C4B1 was catabolized more rapidly than C4A3 in patients with pathological complement activation but not in control subjects. This difference could reflect the relatively greater extravascular distribution (i.e. EV:IV ratio) of C4B at sites of immune complex deposition or, alternatively, different rates of catabolism of inactive C4 isotypes (iC4b).